Ordine pubblico ideale e materiale: quale libertà religiosa? (Stato, Chiese e pluralismo confessionale, 2024)
Ideal and material public order: what religious freedom?ABSTRACT: The limits to the right to religious freedom, both implicit and explicit, have undergone numerous transformations over time. This evolution reflects the changing significance attributed, over the years, to the various interests underlying these restrictions. The concept of ideal public order, safeguarded by the Fascist legislature, contrasts sharply with the material public order, which is the focus of certain criminal provisions. The latter aligns closely with the notion of security, identified in some constitutional norms as a limitation on freedom. In delineating the boundaries of these limits, particular attention must be paid to evaluating the threshold at which the legal system intervenes restrictively. Premature restrictions risk reverting to an idealized interpretation of public order as a constraint on individual freedom.SOMMARIO: 1. Introduzione: i limiti al diritto di libertà religiosa nei lavori preparatori alla Carta costituzionale - 2. Dall’ordine pubblico ideale all’ordine pubblico materiale: il nodo della soglia di intervento dello Stato - 3. Brevi conclusioni: la richiesta di specifici elementi da cui evincere la necessità della tutela (nella giurisprudenza della CEDU).